O-GlcNAcylation of Kinases - Dias, Wagner B. (2012)
Recent evidence indicates that site-specific crosstalk between O-GlcNAcylation and phosphorylation and the O-GlcNAcylation of kinases play an important role in regulating cell signaling. However, relatively few kinases have been analyzed for O-GlcNAcylation. Here, we identify additional kinases that are substrates for O-GlcNAcylation using an in vitro OGT assay on a functional kinase array. Forty-two kinases were O-GlcNAcylated in vitro, representing 39% of the kinases on the array. In addition, we confirmed the in vivo O-GlcNAcylation of three identified kinases. Our results suggest that O-GlcNAcylation may directly regulate a substantial number of kinases and illustrates the increasingly complex relationship between O-GlcNAcylation and phosphorylation in cellular signaling.